Study of electrical conduction in nanostructured Se2.5Ge1-xSnx (x=0, 0.3, 0.5) thin films. (2019) - Deepika,; Singh, Hukum; Saxena, N.S.
Abstract: Thin films of nanostructured Se2.5 Ge1-x Snx (x=0, 0.3, 0.5) glassy alloys were prepared using physical vapor condensation method. The films were characterized using TEM, which confirmed the formation of nanorods in the samples. The I-V characteristics of so-prepared thin films were recorded on Keithley electrometer at various temperatures ranging from 303-373K. The dc electrical conductivity was found to increase with increase in Sn concentration in the Se-Ge system. Two conduction mechanisms were observed in the samples viz. hopping conduction in lower temperature range (303-333K) and thermally activated conduction in higher temperature range (333-373K). Both the samples were found to follow the Mott's 3D VRH model in lower temperature range. It was also observed that conductivity increases on Sn addition to Se-Ge system. This increase was due to conduction by loosely bound electrons of Sn. Further, it was also found that nanostructure formation increases the conductivity of the system compared to bulk Se-Ge-Sn system.